ANALISIS IMPLEMENTASI TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN PERSEROAN DI KECAMATAN KEMBANG JANGGUT KALIMANTAN TIMUR: Analysis Of The Implementation Of Corporate Social And Environmental Responsibility In Kembang Janggut District East Kalimantan - Richo Andriyanto; Sri Bakti Yunari (Reformasi Hukum Trisakti, 2024)
PT. REA Kaltim Plantations is a large-scale oil palm plantation company in Kembang Janggut District, East Kalimantan. This research aims to analyze the implementation of social and environmental responsibility (TJSL) by companies, with a focus on environmental aspects. The problem formulation in this research is how to implement social and environmental responsibility (TJSL) at PT. REA Kaltim Plantations which is environmentally based and what obstacles the company faces in TJSL at PT. REA Kaltim Plantations in its implementation. This research uses empirical research methods using a qualitative approach. The results of research and discussions show that the company has implemented programs related to TJSL, but the achievements are considered not optimal. Some notes of improvement include, among others, the effectiveness of the program in empowering communities, reporting transparency, and active participation in building local sustainability. Companies also face challenges such as the complexity of community needs and environmental dynamics. The conclusion of this research is that companies need to improve TJSL implementation in order to make a greater contribution to sustainable development and welfare of local communities. Recommendations are given to improve the quality and sustainability of the TJSL program by the company.